Innovations Classification Model in Online Sportsbook Betting - Iliev, Petko (Computer Science and Interdisciplinary Research Journal, 2025)
This paper examines the horizontal and vertical cuts of online bookmakers. On this basis, possible classes and subclasses of innovations in online sports betting are theoretically presented. To increase the accuracy of the model, the definition of the groups takes into account the analysis of multiple websites in the field. A classification model with classes, subclasses, and groups covering currently available innovations is proposed.